Scientific Management of the Contact Center in the Singaporean market - Yang, Guo Xiao Corthia (2009)
The Singaporean call center industry is facing managerial issues in the area of retaining Singaporean call center agents. Attrition rate of call center agents is a common issue in many call centers and the practice of Taylorism in call center has often been cited as the possible cause. However, there have been no authoritative studies done in this area that address the Singaporean market specifically. Therefore, it is the objective of this paper is to verify the Hypothesis that the practice of Taylorism is the main cause of high attrition rate among Singaporean call center agents. The second Hypothesis of the paper is the practice of good Human Resource Management strategy can serve to relieve the impact of Taylorism in the attrition rate of Singaporean call center agents. The testing these hypotheses are conducted by using survey that was conducted through the administration of a 18 questions questionnaire that was distributed to 100 Singaporean call center agents and this information is supplemented by interviews conducted with the call center managers of 3 companies. The call center agents are selected from 3 call centers based in Singapore. The findings of the paper fully proved the validity of the Hypothesis and recommendations are provided at the end of this paper. More importantly, the findings also highlighted the positive correlation that existed between the various variable that 5 was tested in the surveys. This indicates that, despite the positive results of the survey, there are other factors that should be considered in the area of reducing attrition rate of Singaporean call center agents.